Molecular Surveillance and Burden of Plasmodium falciparum Isolate to the Resistance of Artemisinin and Mefloquine-based Therapy among Febrile Subjects in Ilorin Metropolis, North-Central Nigeria - Nassar, Adebayo Sulaiman; Bakarey, Adeleye Solomon; Abubakar, Abdulazeez Aderemi; Oluwagbemiga, Michael Adeleke; Alabi, Shukurat Yetunde; Hamzat, Monsurat Bidemi; Olawuyi, Clement Oladayo (Journal of Advances in Microbiology, 2021)
Introduction: Artemisinin-based combination treatments (ACTs) such as Artemisinin and mefloquine are generally accepted as the best forms of therapy for uncomplicated falciparum malaria and usually exceed more than 90% effectiveness. However, the problem of resistance to the target parasites remains a great challenge especially within the northcentral Nigeria. Therefore this study aimed to assess the burden of resistance of Plasmodium falciparum to artemisinin and Mefloquine from the blood smear febrile patients attending tertiary health facility in Ilorin, Nigeria. Methodology: The study was carried among two hundred and one (201) consented febrile individuals age ranged 1-46 years (Mean=22.7 years; M=39; F=61) between May and August 2019. Blood samples collected were subjected to Microscopy using Giemsa staining technique and Rapid diagnostic test (RDT) using (SD BIOLINE Malaria Ag P.f/Pv, South Korea) kit  to detect the presence of P. falciparum A semi-structured questionnaire was used to capture demographic and other relevant information while data was analysed with SPSS version 21. Results: Of the 201 samples tested, 113 (56.5%) were positive for Microscopy and RDT. Fifty of the positive samples for Microscopy and RDT were further subjected to PCR technique for the presence of Plasmodium falciparum and amplification of Kelch13 and FR1gene mutation of which one (2.0%) showed amplification for the PfKelch13 gene mutation for artemisinin while none was recorded for FR1 gene mutation in case of Mefloquine. Conclusion: This study reported a high rate of detection for Plasmodium falciparum using microscopy and RDT but moderately low rate of resistance to amplification for the PfKelch13 gene mutation for artemisinin but none for FR1 gene mutation for mefloquine by PCR. This suggests a clue for further monitoring of the artemisinin and Mefloquine resistance by detection of some molecular markers in k13 and FRI genes of Plasmodium in our communities in Nigeria.